Penggunaan Media Gambar dan Metode Demonstrasi Untuk Meningkatkan Kemampuan Mengidentifikasi Organ Pernapasan Manusia Pada Siswa Kelas V SDN 4 Jepon Semester 1 Tahun Ajaran 2015/2016 - Salam, Salam; , Drs. Andi Haris Prabawa, M.Hum (2015)
There are still many students who get difficulties in Natural Science learning, especially in human respiration organ material, it's shown by low result learning or students don't reach passing grade score yet, students just reach 15% or just 5 students who get good score, and 15 students don't reach it yet (they don't reach minimum score 7,5). Based on the file that researcher gets, students don't have comprehension about human respiration organ yet. Besides that, in Natural Science learning activity, teacher still uses conventional method, it means teacher's learning activity is just speech, without using props, and less to make students become creative and learning activity is not interesting g yet, so learning activity doesn't have interaction between teacher and students, students with students, which causes in learning result don't reach enough score yet, in classical and in individual. The research purpose is to know student's successful in 5th grade students of State Elementary School 5 Jepon in human respiration organ concept learning with using demonstration method and picture media. Learning result is : 1) Pre Cycle, average score which is gotten by students just 64 and 46,7% passing grade. 2) 1st Cycle, average score in 1st cycle increases to 85 with 80% passing grade. But the result which is reached in 1st cycle still has 3 students who need attention. It is caused by material comprehension is not maximum yet. 3) 2nd cycle, the result which is reached can get passing grade learning score with classical or individual. Student's average score is 93,3 with 100% passing grade score and complete the standard which is decided by school, 75. Based on research result, teacher needs to give more material comprehension to students with student's ability hope more increases.